Characterization of Rhizobia Isolated from Tigray Soil and Assessment of Their Effect on Germination and Seedling Vigor of Wheat and Field Pea - Etsay Mesele; Ashenafi Teklay Yaekob; Melaku Mekonen Kasegn; Birhanu Kahsay Meresa; Micheale Yifter Weldemichael; Yisehak Tsegaye Redda; Genet Gebreyohanns; Roza Hadush; Tesfakiros Semere (International Journal of Agronomy)
Nowadays, the inoculation of plant growth-promoting rhizobia in leguminous and nonleguminous crops is given great emphasis as it improves germination and seedling vigor, resulting in increased yields. In this study, 32 rhizobia isolates were obtained from five different sampling sites in Tigray, Ethiopia. Based on morphological, biochemical, and confirmatory tests, including sugar fermentation, the isolates were identified as belonging to the rhizobia genera. In vitro assessment of plant growth-promoting properties revealed that all isolates produced indole-acetic-acid, ammonia, and solubilized phosphate, except TA8, which did not solubilize phosphate. Only 3 isolates (TA1, TA2, and TA8) produced hydrogen cyanide, so they can be used as biocontrol agents. Nineteen isolates showed a growth reduction activity against Fusarium oxysporum, with a percent inhibition range of 34.2%–65.8%. All isolates tolerated a pH range of 4.0–9.0. The isolates showed growth variations in various temperatures and salt concentrations. A few isolates were tolerant up to 45°C temperature and 6% (w/v) CaCl2 and NaCl concentrations. Inoculation of the isolates to wheat seeds increased seed germination, seedling shoot/root length, and seedling vigor index compared to the positive and negative controls. Isolates KO3, KO4, ME3, and TA5 increased seed germination by 4%. KO1 (11.60 cm) and TA7 (11.70 cm) showed a significantly enhanced shoot length, and ME3 showed a maximum root length (13.90 cm). SH1, KO2, and the positive control showed a significant (P≤0.05) increase in pea seed germination (by 20%) compared to the negative control. The positive control had the longest field pea shoot (5.70 cm), and isolate TA9 had the longest field pea root (5.32 cm) compared to the negative control. Generally, the wheat and field pea seedlings responded differently to the inoculation of different isolates. This study shows that Tigray soils harbor a variety of rhizobia species, which can be used as plant growth-promoting and biocontrol agents.